ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN MEMBELI ULOS BATAK TOBA PADA TOKO SIBORO ULOS PEMATANGSIANTAR - Spianus Halawa (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
This study aims to analyze the factors that influence consumers in buying Toba Batak Ulos at the Siboro Ulos Pematangsiantar Store. Using qualitative and quantitative research methods. The samples studied were 86 respondents. The analysis technique used is factor analysis techninque. The results showed that it had formed into 3 factors, namely social factors, situational factors and psychological factors. In the factor analysis, the KMO measure of adequancy value is 0.566 > 0.5 and the anti-image is MSA > 0.5. From the results, the total variance explained shows that the total initial sosial eingenvalues are 1,972 > 1, the total situational initial eigenvalues are 1,790 > 1, and the total psychological initial eingenvalues are 1,276 > 1. Thus, the social factor is the most dominant in this study. Keywords : Purchase decisions; psychological factors; situational factors, and social factors.